Bio-reduction of tetrachloroethen using a H2-based membrane biofilm reactor and community fingerprinting - Karatas, Serdar; Hasar, Halil; Taskan, Ergin; Ozkaya, Bestarnin; Sahinkaya, Erkan (Pergamon-Elsevier Science Ltd, 2014)
Chlorinated ethenes in drinking water could be reductively dechlorinated to non-toxic ethene by using a hydrogen based membrane biofilm reactor (H-2-MBfR) under denitrifying conditions as it provides an appropriate environment for dechlorinating bacteria in biofilm communities. This study evaluates the reductive dechlorination of perchloroethene (PCE) to non-toxic ethene (ETH) and comparative community analysis of the biofilm grown on the gas permeable membrane fibers. For these purposes, three H-2-MBfRs receiving three different chlorinated ethenes (PCE, TCE and DCE) were operated under different hydraulic retention times (HRTs) and H-2 pressures. Among these reactors, the H-2-MBfR fed with PCE (H-2-MBfR 1) accomplished a complete dechlorination, whereas cis-DCE accumulated in the TCE receiving H-2-MBfR 2 and no dechlorination was detected in the DCE receiving H-2-MBfR 3. The results showed that 95% of PCE dechlorinated to ETH together with over 99.8% dechlorination efficiency. Nitrate was the preferred electron acceptor as the most of electrons generated from H-2 oxidation used for denitrification and dechlorination started under nitrate deficient conditions at increased H-2 pressures. PCR-DGGE analysis showed that Dehalococcoides were present in autotrophic biofilm community dechlorinating PCE to ethene, and RDase genes analysis revealed that pceA, tceA, bvcA and vcrA, responsible for complete dechlorination step, were available in Dehalococcoides strains. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Perchloroethene; Reductive dehalogenation; Membrane biofilm reactor; Hydrogen; Dehalococcoides